2019
DOI: 10.1142/s0218625x18501974
|View full text |Cite
|
Sign up to set email alerts
|

SYNTHESIS AND CHARACTERIZATION OF Fe–ZnO THIN FILMS FOR ANTIMICROBIAL ACTIVITY

Abstract: Pure and Fe-doped zinc oxide (ZnO) sol–gel thin films were deposited by spin-coating process. Pure ZnO and Fe–ZnO films, containing Fe of 2–8[Formula: see text]wt.%, were annealed at 500∘C for 2[Formula: see text]h. All prepared thin films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and UV–visible (UV–vis) spectroscopy. XRD studies show the polycrystalline nature with hexagonal wurtzite structure of pure ZnO and Fe–ZnO thin films. The crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…AL-Jawad et al observed a similar enhancement of antibacterial activity against S. aureus and E. coli in Ag-doped ZnO thin films [31]. Fe-doped ZnO thin films also exhibited a better antibacterial response under UV light irradiation against S. aureus and E. coli [32].…”
Section: Analysis Of Morphology and Elementsmentioning
confidence: 79%
“…AL-Jawad et al observed a similar enhancement of antibacterial activity against S. aureus and E. coli in Ag-doped ZnO thin films [31]. Fe-doped ZnO thin films also exhibited a better antibacterial response under UV light irradiation against S. aureus and E. coli [32].…”
Section: Analysis Of Morphology and Elementsmentioning
confidence: 79%
“…It observes that the average crystal size of the R-MWCNTs and F-MWCNTs are about (3.27 and 3.19) nm, respectively. the average crystal size of high intensity peaks calculated from the Scherer's equation ( 1) is about 25.43 nm [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that a correct comparison of the bactericidal efficacy of various materials with Fe nanoparticles is almost impossible due to the difference in many key parameters: the film elemental and phase composition, the Fe loading dose, the degree of Fe nanoparticle oxidation and the type of their agglomeration, the irradiation time and power of the source used, as well as the type of used bacterial cultures and their initial concentration. In terms of bactericidal efficiency, the Fe/TiCaSiCON films (100% reduction in CFUs after 8 h) outperform many other systems, for example, Fe/ZnO and Fe/TiO 2 films. Note that the above-mentioned Fe/ZnO and Fe/TiO 2 samples were tested according to the protocol providing for the UV irradiation of a sample with a bacterial suspension on the surface, which could lead to overestimated bactericidal effect.…”
Section: Discussionmentioning
confidence: 99%